In Vitro Estimation of Lead Content in Nepalese Traditional Ayurvedic Medicines Commonly Used in Children - Ojha, Anil (Journal of Nepal Paediatric Society, 2013)
Introduction: Ayurvedic remedies are popularly used in practice for long time in Nepal. It is regarded as safe and free from side effects. However there are published reports of the high content of heavy metals like lead in such preparations. No such study has been done in Nepal looking at the lead content in ayurvedic preparations. The aim of this study was to detect the level of lead in commonly used ayurvedic remedies used in paediatric population if any. Materials and Methods: Seventeen samples were selected for lead estimation based on frequency of prescription and over the counter dispense. All of them were analyzed using Atomic Absorption Spectrophotometer (AAS) 6300 using flame mode. Results: None of the samples had detectable level of lead in parts per billion. Conclusion: Though this study did not detect lead in the seventeen samples of ayurvedic medicine, a larger study is needed involving large samples of these medicines with use of more sensitive equipment for testing. DOI: http://dx.doi.org/10.3126/jnps.v33i2.8314 J Nepal Paediatr Soc. 2013; 33(2):103-105